Proyecto de Factibilidad para la creación del LODGE "Paraiso Escondido",en la Parroquia de Santa Rosa, Cantón Chaco, Provincia del NAPO. - Calle Paredes, Juana Jaqueline (2012)
The main objective of this work is to determine its feasibility of implementing it and that it meets its expectations and meets the needs of domestic and foreign visitors seeking new tourism alternatives trying to break a daily routine and know the biodiversity that Ecuador offers. Therefore, this research work provides several ways to analyze the feasibility of the project through market research, technical study, administrative - legal, economic studies - financial and project evaluation, conducted through field research and quantitative analysis methods. This project is about providing accommodation, restaurant and recreation, offered to your potential clients with quality services, excellent comfort rooms, where tourists can successfully rest after visiting the range of interest associated with the environment. In order to obtain results, a series of studies were performed, they were: a market study in which it was determined the supply of tourist services and indirect demand in el Chaco canton which received 7,100 tourists in 2010 according to the Tourism Unit, an inventory of natural and cultural attractions this canton owns was carried out. Some marketing strategies in order to promote tourism in the Lodge were established.